Evaluation of radiation sensitivity and mating performance of Glossina brevipalpis males. - Chantel J de Beer; Percy Moyaba; Solomon N B Boikanyo; Daphney Majatladi; Hanano Yamada; Gert J Venter; Marc J B Vreysen (Public Library of Science (PLoS), 2017)
BACKGROUND:Area-wide integrated pest management strategies that include a sterile insect technique component have been successfully used to eradicate tsetse fly populations in the past. To ensure the success of the sterile insect technique, the released males must be adequately sterile and be able to compete with their native counterparts in the wild. METHODOLOGY/PRINCIPAL FINDINGS:In the present study the radiation sensitivity of colonised Glossina brevipalpis Newstead (Diptera; Glossinidae) males, treated either as adults or pupae, was assessed. The mating performance of the irradiated G. brevipalpis males was assessed in walk-in field cages. Glossina brevipalpis adults and pupae were highly sensitive to irradiation, and a dose of 40 Gy and 80 Gy induced 93% and 99% sterility respectively in untreated females that mated with males irradiated as adults. When 37 to 41 day old pupae were exposed to a dose of 40 Gy, more than 97% sterility was induced in untreated females that mated with males derived from irradiated pupae. Males treated as adults with a dose up to 80 Gy were able to compete successfully with untreated fertile males for untreated females in walk-in field cages. CONCLUSIONS/SIGNIFICANCE:The data emanating from this field cage study indicates that, sterile male flies derived from the colony of G. brevipalpis maintained at the Agricultural Research Council-Onderstepoort Veterinary Institute in South Africa are potential good candidates for a campaign that includes a sterile insect technique component. This would need to be confirmed by open field studies.